Dispersive electrolyte additive for battery and preparation method thereof
Micron-scale metal deposits are prepared by electrodeposition method and reacted with gas to form micro-nano-level metal compounds, which solves the problems of poor stability and safety hazards of existing electrolyte additives, and improves the battery cycle performance and service life.
Patent Information
- Application Number
- CN202411551196.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
Existing electrolyte additives have poor stability and are easily depleted during long cycles. Some additives will cause polymerization exothermic and safety hazards, and will have a great impact on the human body and the environment.
High-purity micron-scale metal deposits were prepared in the electrolyte by electrodeposition method, and reacted with gas to form micro-nano-scale metal compounds as dispersed electrolyte additives for batteries.
It realizes uniform dispersion of additives in the electrolyte, improves battery circulation performance and service life, and reduces production costs and environmental pollution risks.
Smart Images

Figure CN119419362A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary battery electrolyte materials, and in particular relates to a dispersed electrolyte additive for a battery and a preparation method thereof. Background Art
[0002] With the growing global demand for clean energy and portable electronic devices, the importance of secondary batteries as efficient, rechargeable energy storage systems has become increasingly prominent. As the key medium in the battery reaction site, the electrolyte directly affects the performance and service life of the battery. In high-performance metal batteries, the electrolyte needs to have high ionic conductivity, low resistivity, and good chemical stability to ensure efficient operation and long-term stability of the battery. At the same time, the electrolyte needs to maintain stable chemical properties to avoid safety issues such as thermal runaway and short circuit.
[0003] In order to solve these problems, researchers have proposed a variety of solutions. Among them, electrolyte additives have become a hot topic in electrolyte research due to their small dosage and quick effect. However, traditional electrolyte additives have the following shortcomings: (1) poor stability, and they will participate in the electrochemical reaction process and are easily exhausted during long cycles; (2) some additives will polymerize and release heat, affecting battery safety; (3) some additives will cause health hazards when in contact with the human body, and improper handling will also cause pollution to the environment.
[0004] Therefore, new additives have emerged, such as suspension additives, slow-release additives, biomass additives, etc. Among them, suspension additives have once again become the focus of research due to their good cycle stability, not easy to be exhausted, higher safety, and less impact on the human body and the environment. However, suspension additives have also exposed some problems during use, the most prominent of which is that they cannot be guaranteed to be evenly dispersed in the electrolyte.
[0005] Studies have shown that micro-nano particles can help improve the dispersibility of additives, so micro-nano particles can greatly improve the performance of secondary battery electrolytes. However, the preparation of micro-nano particles currently has problems such as high cost, high energy consumption, complex process and environmental pollution. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a method for synthesizing efficient and low-cost micron inorganic particles. By precisely controlling the key parameters in the electrodeposition process, fine regulation of the metal deposition morphology is achieved, and then reacting with different substances to synthesize a series of high-performance micro-nano metal compounds. The synthesized micro-nano particles are used as new suspended additives to optimize battery performance.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing a dispersed electrolyte additive for a battery, using an active metal as an anode, preparing a metal deposit on a cathode current collector in an electrolyte by an electrodeposition method, and mixing the metal deposit with a gas to react to obtain a micro-nano metal deposit, which is the dispersed electrolyte additive for the battery.
[0010] The present invention adopts the method of electrodeposition to prepare metal deposits. During the electrodeposition process, the current passes through the migration of positive and negative ions in the electrolyte solution, and an oxidation-reduction reaction of gaining and losing electrons occurs on the electrode. Therefore, the obtained metal deposit has high purity, uniform dispersion, and small particle size, and micron-level deposit particles can be obtained. And by regulating the conditions and parameters in the deposition process, the particle size of the obtained metal deposit can be adjusted. The metal deposit is then mixed with a gas for reaction, and the obtained metal compound product is a micro-nano-level particle, which can ensure uniform dispersion when used as an electrolyte additive.
[0011] Furthermore, the current density of the electrodeposition method is 0.1-5 mA·cm -2 , deposition capacity is 0.5-50mAh·cm -2 , the deposition temperature is room temperature.
[0012] The change of current density in the electrodeposition method will directly affect the size of the metal deposit. The larger the current, the smaller the size. Therefore, the present invention can realize the preparation of metal deposits with smaller sizes (such as a few nanometers or tens of nanometers); the change of deposition capacity will affect the stacking morphology of the metal deposit in the vertical direction.
[0013] The morphology of metal deposits can be filament-shaped, columnar, block-shaped, spherical, flake-shaped, etc. Their size and specific morphology are closely related to the electrodeposition conditions. By precisely controlling and selecting the deposition conditions, metal deposits can be obtained, creating conditions for the subsequent preparation of micron metal compounds (dispersed electrolyte additives for batteries).
[0014] Furthermore, the active metal is lithium, sodium, potassium, zinc or magnesium.
[0015] Furthermore, the cathode current collector can be selected from current collectors of different materials, such as copper, titanium, tungsten, nickel, stainless steel, carbon and composite current collectors, etc.; and current collectors of different structures, such as porous, planar, etc. The morphology of the metal deposits on its surface will be different depending on the choice of current collector material and structure.
[0016] Furthermore, the electrolyte includes a solvent and a metal salt; the solvent is an ester solvent and / or an ether solvent.
[0017] Furthermore, the electrolyte also includes additives.
[0018] The morphology of metal deposits on the surface of the electrolyte will be different depending on the choice of electrolyte.
[0019] Furthermore, the ester solvent includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the ether solvent includes one or more of ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF) and dioxolane (DOL).
[0020] Furthermore, the metal salt is selected differently according to the type of battery. Furthermore, the metal salt can be a lithium salt, a sodium salt, a potassium salt, a zinc salt or a magnesium salt. More specifically, for example, lithium batteries use lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), etc.; sodium batteries use sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium bis(oxalate borate) (NaBOB), sodium bis(trifluoromethanesulfonyl imide) (NaTFSI), sodium bis(fluorosulfonyl imide) (NaFSI), etc.; potassium batteries use potassium hexafluorophosphate (KPF6), potassium tetrafluoroborate (KBF4), potassium bis(trifluoromethanesulfonyl imide) (KTFSI), potassium bis(fluorosulfonyl imide) (KFSI), etc.; and commonly used salts for zinc and magnesium batteries.
[0021] Furthermore, the gas is oxygen, nitrogen, hydrogen, water vapor, sulfur vapor, carbon dioxide, iodine vapor, bromine vapor and a mixture thereof, and the gas reacts with the deposited metal deposit to generate corresponding metal oxides, metal nitrides, metal hydrides, metal hydroxides, metal sulfides, metal carbonates, metal halides or metal compounds of a mixture thereof.
[0022] The second technical solution of the present invention:
[0023] A dispersed electrolyte additive for a battery prepared by the preparation method.
[0024] Furthermore, the particle size of the dispersed electrolyte additive for the battery is 0.5-2.5 μm.
[0025] Compared with the prior art, the preparation method of the morphology-controllable micro-nano active metal compound (dispersed electrolyte additive for battery) provided by the present invention has the advantages that the morphology and size of the micro-nano particles can be precisely controlled, and the product has clear directionality, and the production cost is greatly reduced. The product can be used as the corresponding metal secondary battery suspension electrolyte additive, which can greatly improve the battery cycle performance and extend the battery life. In addition, the preparation process is simple and will not cause environmental pollution and other problems. Specifically:
[0026] 1. By precisely controlling the key parameters in the electrodeposition process, the present invention achieves fine control of the morphology and size of metal deposition, provides a rich morphological basis for subsequent chemical reactions, and successfully synthesizes a variety of high-performance micro-nano metal compounds with different morphologies and sizes.
[0027] 2. The reaction conditions and the selection of reactants are optimized. Pure metal deposits are directly selected to react with a certain specific gas to synthesize metal compounds in a direction. The reactants are single and pure, which reduces the occurrence of side reactions, improves the reaction efficiency, improves the purity of the product, and reduces the subsequent processing costs.
[0028] 3. The prepared micro-nano compounds are used as additives for suspended electrolytes of secondary batteries. They have good dispersibility in the electrolyte, participate in the battery cycle but are not consumed, have good stability in long cycles, improve the electrolyte solvation structure, promote uniform ion transmission, and extend the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0030] Figure 1 This is a scanning electron microscope (SEM) image of the metal deposit (deposited lithium) prepared in Example 1;
[0031] Figure 2 This is a scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 1;
[0032] Figure 3 The X-ray diffraction (XRD) pattern of the micro-nano metal compound prepared in Example 1;
[0033] Figure 4 This is a scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 2;
[0034] Figure 5 This is a scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 3;
[0035] Figure 6 This is a scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 4;
[0036] Figure 7 The graph is a test result of the cycle performance of a full battery with and without the lithium carbonate additive prepared in Example 1 in the electrolyte;
[0037] Figure 8 The graph is a test result of the cycle performance of a full battery with and without the lithium carbonate additive prepared in Example 5 in the electrolyte;
[0038] Fig. 9 The graph is a test result of the cycle performance of a full battery with and without the lithium carbonate additive prepared in Example 6 in the electrolyte;
[0039] Fig.10 This is a scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 7. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] An embodiment of the present invention proposes a method for preparing a dispersed electrolyte additive for a battery, wherein an active metal is used as an anode, a metal deposit is prepared on a cathode current collector by an electrodeposition method in an electrolyte, and the metal deposit is mixed with a gas for reaction to obtain the dispersed electrolyte additive for a battery.
[0046] In a preferred embodiment of the present invention, the current density of the electrodeposition method is 0.1-5 mA·cm -2 , deposition capacity is 0.5-50mAh·cm -2 The deposition temperature is room temperature (room temperature in the embodiment of the present invention refers to 25±2° C.).
[0047] Preferably, the current density of the electrodeposition method is 0.5 mA·cm -2 , the deposition capacity is 0.5 mAh cm -2 .
[0048] The change of current density in the electrodeposition method will directly affect the size of the metal deposits, and the change of deposition capacity will affect the stacking morphology of the metal deposits in the vertical direction.
[0049] The morphology of metal deposits can be filament-shaped, columnar, block-shaped, spherical, flake-shaped, etc. Their size and specific morphology are closely related to the electrodeposition conditions. By precisely controlling and selecting the deposition conditions, metal deposits can be obtained, creating conditions for the subsequent preparation of micron metal compounds (dispersed electrolyte additives for batteries).
[0050] In a preferred embodiment of the present invention, the active metal is lithium, sodium, potassium, zinc or magnesium.
[0051] Preferably, the anode active metal is lithium.
[0052] In a preferred embodiment of the present invention, the cathode current collector can be selected from current collectors of different materials, such as copper, titanium, tungsten, nickel, stainless steel, carbon and composite current collectors, etc.; and current collectors of different structures, such as porous, planar, etc. The morphology of the metal deposits on its surface will be different depending on the choice of current collector material and structure.
[0053] Preferably, the cathode current collector is copper.
[0054] In a preferred embodiment of the present invention, the electrolyte includes a solvent and a metal salt, the solvent is an ester solvent and / or an ether solvent, and the metal salt is a lithium salt, a sodium salt, a potassium salt, a zinc salt or a magnesium salt.
[0055] In a preferred embodiment of the present invention, the electrolyte further includes an additive.
[0056] Preferably, the ester solvent includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the ether solvent includes one or more of ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF) and dioxolane (DOL).
[0057] Preferably, the type of the metal salt is selected according to the type of battery, for example, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), etc. in lithium batteries; sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium bis(oxalatoborate) (NaBOB), sodium bis(trifluoromethanesulfonyl imide) (NaTFSI), sodium bis(fluorosulfonyl imide) (NaFSI), etc. in sodium batteries; potassium hexafluorophosphate (KPF6), potassium tetrafluoroborate (KBF4), potassium bis(trifluoromethanesulfonyl imide) (KTFSI), potassium bis(fluorosulfonyl imide) (KFSI), etc. in potassium batteries; and commonly used salts in zinc and magnesium batteries.
[0058] Preferably, the additive is LiNO3.
[0059] In a preferred embodiment of the present invention, the electrolyte is 1M LiTFSI-DOL, 1M LiPF6-DMC:FEC or 1MLiTFSI-DOL:DME (1:1) + 1wt% LiNO3, wherein 1M LiTFSI-DOL means that LiTFSI is dissolved in DOL, and the concentration of LiTFSI in the electrolyte is 1M, 1M LiPF6-DMC:FEC means that LiPF6 is dissolved in a mixture of DMC and FEC (volume ratio of 4:1), and the concentration of LiPF6 in the electrolyte is 1M, 1M LiTFSI-DOL:DME (1:1) + 1wt% LiNO3 means that LiPF6 is dissolved in a mixture of DMC and FEC (volume ratio of 4:1), and the concentration of LiPF6 in the electrolyte is 1M, and the concentration of the additive LiNO3 in the mixture of DMC and FEC is 1wt%.
[0060] In a preferred embodiment of the present invention, the gas is oxygen, nitrogen, hydrogen, water vapor, sulfur vapor, carbon dioxide, iodine vapor, bromine vapor and a mixture thereof, and the gas reacts with the deposited metal deposit to generate corresponding metal oxides, metal nitrides, metal hydrides, metal hydroxides, metal sulfides, metal carbonates, metal halides or metal compounds of a mixture thereof. More preferably, the gas is carbon dioxide.
[0061] All raw materials used in the examples of the present invention are commercially available.
[0062] The technical solution of the present invention is further illustrated by the following embodiments.
[0063] Example 1
[0064] A lithium-copper half-cell was assembled with lithium as the anode, copper foil as the cathode current collector, and 1 M LiTFSI-DOL as the electrolyte. -2 , the deposition capacity is 0.5 mAh cm -2 The electrodeposition was carried out at room temperature. After the deposition was completed, the battery was disassembled in a glove box, and the residual electrolyte on the lithium surface of the copper foil was washed with DOL to obtain a metal deposit (deposited lithium).
[0065] The deposited lithium on the surface of the copper foil is placed in a fume hood and carbon dioxide is introduced to fully react to obtain micro-nano metal compounds.
[0066] The scanning electron microscope (SEM) image of the metal deposit (deposited lithium) prepared in Example 1 is shown in Figure 1 It can be seen that there are micro-nano particles in the deposited lithium, and the particles are blocky with an average particle size of 1.434μm.
[0067] The scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 1 is shown in Figure 2 It can be seen that the morphology after oxidation remains basically unchanged, with an average particle size of 1.3648 μm, proving that the deposited lithium can maintain its basic morphological characteristics before and after oxidation.
[0068] The X-ray diffraction (XRD) pattern of the micro-nano metal compound prepared in Example 1 is shown in Figure 3 It can be found that the product of the deposited lithium after sufficient reaction in carbon dioxide is mostly lithium carbonate, which contains a small amount of lithium hydroxide.
[0069] Example 2
[0070] Same as Example 1, except that 1M LiPF6-DMC:FEC is used as the electrolyte.
[0071] The scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 2 is shown in Figure 4 It can be seen that the morphology after oxidation is filament-like, and the average strip width is 0.679 μm. Compared with Example 1, the change of the electrolyte system affects the lithium deposition morphology and affects the morphology of the compound.
[0072] Example 3
[0073] The same as Example 1, except that 1M LiTFSI-DOL:DME (1:1) + 1wt% LiNO3 is used as the electrolyte.
[0074] The scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 3 is shown in Figure 5 It can be seen that the morphology after oxidation is columnar, and the average columnar width is 1.07 μm. Compared with Example 1, the change in electrolyte type has an impact on the lithium deposition morphology and affects the morphology of the compound.
[0075] Example 4
[0076] Same as Example 1, except that the current density is 0.1 mA·cm -2 .
[0077] The scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 4 is shown in Figure 6 It can be seen that the average particle size is 2.48 μm. Compared with Example 1, the particle size has a significant increasing trend, proving that when the current density decreases, the lithium deposition particle size will increase, and then the compound particle size will also increase accordingly.
[0078] Performance Testing
[0079] The micro-nano metal compound (lithium carbonate) prepared in Example 1 was used as a dispersed electrolyte additive for batteries to prepare a 1M LiTFSI-DOL electrolyte containing 0.5wt% lithium carbonate by mass, and assembled into a lithium||lithium iron phosphate full battery. Another lithium iron phosphate full battery without lithium carbonate additive in the electrolyte was prepared and cycled at 0.4C and low temperature of -10°C. The results are shown in FIG. Figure 7 It can be seen that the cycle performance of the lithium carbonate battery prepared in Example 1 can exceed 200 cycles, while the capacity of the full battery assembled with the electrolyte without the lithium carbonate additive begins to decrease after 50-60 cycles, indicating that the micro-nano metal compound prepared by the present invention can be used as a dispersed electrolyte additive for batteries.
[0080] Example 5
[0081] Same as Example 1, except that the current density is 5 mA·cm -2 .
[0082] Performance Testing
[0083] The micro-nano metal compound prepared in Example 5 was used as a dispersed electrolyte additive for a battery to prepare a 1M LiTFSI-DOL electrolyte containing 0.5wt% lithium carbonate by mass, and assembled into a lithium||lithium iron phosphate full battery. Another lithium iron phosphate full battery without lithium carbonate additive in the electrolyte was prepared and cycled at 0.4C and low temperature of -10°C. The results are shown in FIG. Figure 8 It can be seen that under this condition, the capacity of the battery starts to decrease after 120 cycles, compared with the full battery assembled with the electrolyte without lithium carbonate additive (the capacity starts to decrease after 50-60 cycles), which shows that the micro-nano metal compound prepared in Example 5 of the present invention can be used as a dispersed electrolyte additive for batteries with better performance.
[0084] Example 6
[0085] Same as Example 1, except that the deposition capacity is 50 mAh·cm -2 .
[0086] The micro-nano metal compound prepared in Example 6 was used as a dispersed electrolyte additive for a battery to prepare a 1M LiTFSI-DOL electrolyte containing 0.5wt% lithium carbonate by mass, and assembled into a lithium||lithium iron phosphate full battery. Another lithium iron phosphate full battery without lithium carbonate additive in the electrolyte was prepared and cycled at 0.4C and low temperature of -10°C. The results are shown in FIG. Fig. 9 It can be seen that under this condition, the capacity of the battery only decreases when the number of cycles reaches 120. Compared with the full battery assembled with the electrolyte without lithium carbonate additive (the capacity begins to decrease after 50-60 cycles), it shows that the micro-nano metal compound prepared in Example 6 of the present invention can be used as a dispersed electrolyte additive for batteries with better performance.
[0087] Example 7
[0088] Same as Example 1, except that the current density is 1 mA·cm -2 .
[0089] The scanning electron microscope (SEM) image of the micro-nano metal compound prepared in Example 7 is shown in Fig.10 It can be seen that the particle size of micro-nano metal compounds can reach 319-413nm, realizing the preparation of smaller-sized metal deposits.
[0090] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a dispersed electrolyte additive for a battery, characterized in that: Active metal is used as anode, metal deposit is prepared on cathode current collector by electrodeposition in electrolyte, and the metal deposit is mixed with gas for reaction to obtain the dispersed electrolyte additive for battery.
2. The method for preparing a dispersed electrolyte additive for a battery according to claim 1, characterized in that: The current density of the electrodeposition method is 0.1-5 mA·cm -2 , deposition capacity is 0.5-50mAh·cm -2 , the deposition temperature is room temperature.
3. The method for preparing a dispersed electrolyte additive for a battery according to claim 1, characterized in that: The active metal is lithium, sodium, potassium, zinc or magnesium.
4. The method for preparing a dispersed electrolyte additive for a battery according to claim 1, characterized in that: The electrolyte includes a solvent and a metal salt; The solvent is an ester solvent and / or an ether solvent.
5. The method for preparing a dispersed electrolyte additive for a battery according to claim 4, characterized in that: The ester solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, vinylene carbonate and fluoroethylene carbonate; and / or, The ether solvent includes one or more of ethylene glycol dimethyl ether, tetrahydrofuran and dioxolane.
6. The method for preparing a dispersed electrolyte additive for a battery according to claim 1, characterized in that: The gas is oxygen, nitrogen, hydrogen, water vapor, sulfur vapor, carbon dioxide, iodine vapor, bromine vapor and a mixture thereof.
7. A dispersed electrolyte additive for a battery prepared by the preparation method according to any one of claims 1 to 6.